KOMPETENSI ABSOLUT PENGADILAN AGAMA DAN KEKHUSUSAN BERACARANYA PASCA AMANDEMEN UNDANG-UNDANG NOMOR 7 TAHUN 1989 TENTANG PERADILAN AGAMA - Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2016)
Absolute competency Religious Courts after the amendment of Law Number 7 of 1989 both according to Act Number 3 of 2006 on the amendment of Act Number 7 of 1989, and according to Act Number 50 of 2009 on the Second Amendment Act Number 7 of 1989 onReligious Courts become increasingly widespread with the presence of a special Courts in the province of Nangroe Aceh Darussalam, the competence not only in the field of civil law of Islam, but also including Islamic criminal law as well as other competencies stipulated in the by laws. The Religious Courts Competence to grow wider with their competence andadjudicates disputes zakat, infaq, and economic syari’ah, then, specifically with regard tothe absolute competence Religious Competency Courts in examining and deciding disputessyari’ah economy, the parties to the dispute are not only people who are Muslims, butpotencialy also for those non-Muslim who voluntary submit himself to the laws of Islam. Inaddition, with the elimination of the option rights, the Religious Courts also authorized toexamine and decide property disputes and other civil cases related to the object of the dispute is set out in article 49 of Act Number 3 of 2006, when the subject of the dispute is between those who are Muslims. Specificity associated with litigation, with the potential fornon-Muslim people as a subject for dispute resolution in the syari’ah economy on the basis of voluntary submission to Islamic Law, then, the position of the principle of personality toIslamization as a procedural specificity on the Religious Courts as a contained in article 1paragraph 1 of Act Number 7 of 1989 is not absolute again. Another thing that is necessaryand should be regulated, but it is not regulated at all, both in the first amendment , namely Act Number 3 of 2006, and the second amendment, namely Act Number 50 of 2009 on amendment of Act Number 7 of 1989 about Religious Courts relating to the specificity of the hearing of the Religious Courts is a problem charging the case, but with the expansion of its jurisdiction as set forth in Article 49 in conjunction with article 50 of Act Number 3 of 2006, the provisions on court fees, as contained in Article 89 paragraph (1) of Act Number 7 of 1989 is no longer relevant, so if the judge would still apply, it is devinitely potentially also apply to the judge in the case decide imposition of court fee is not fair to the parties, especially for led by won in a yudicial decision.